An Analysis Of Students’ Abilities In Pronuncing Word Stresses Of English Education Section IAIN Bukittinggi Academic Year 2019/2020 - Afri , Kharisma; Prima Dewi, Meri (Jurnal Pendidikan Tambusai, 2022)
The main focus of the research is to find out the level of students ability in pronouncing word stresses by using percentage, the research was due to the problem found some students still incorrectly put the stress within a word. The design of this research was a descriptive quantitative research where the sample was taking by using simple random sampling technique with 20 students as samples. Additionally, the analyzing of the data was done by using pronunciation test. In conclusion, students’ ability in pronuncing word stress of English Education section IAIN Bukittinggi was poor because the percentage of their abilities in pronuncing word stress only reached 43% of all the items.